I09 A Huntington's disease embryonic stem cell phenotypic hts to identify small molecule modulators of mutant huntingtin. (12th September 2022) - Todd, Daniel; Stebbeds, Marta; Thatcher, Emma; Barnard, Amy; Anton, Jeremy; Sienerth, Arnold; Visser, Mijke; Mitchell, Philip; Breccia, Perla; Smith, David; McAllister, George; Haque, Tasir; et al.
Abstract : Huntington's disease (HD) is a neurodegenerative genetic disorder that affects muscle coordination and leads to cognitive decline. HD is caused by a trinucleotide repeat expansion in the huntingtin (HTT) gene, specifically a CAG (polyglutamine) expansion in exon 1 which results in an abnormal mutant protein. HD therapeutic discovery is currently biased towards HTT lowering agents. Encouragingly, a clinical pipeline for DNA/RNA targeted HTT-lowering agents now exists; however, most of these approaches use biological agents, such as ASOs, RNAi and ZFTRs that require invasive administration and have relatively limited biodistribution. To overcome these challenges, we seek to identify novel brain penetrant small molecules with suitable oral dosing that selectively lower mutant HTT protein. To do this, we developed an unbiased phenotypic assay in HD-patient derived, polyQ48 embryonic stem cells (ESC) and screened AstraZeneca's industry-leading 250k EPEC compound library through the Open Innovation Partnership Scheme. Progressed HTT-lowering hits showed good translation in IC50 format; counter-screen and orthogonal assays were then applied to define specificity, selectivity, and putative mechanism of action. One compound was identified for further progression as it displayed a robust and specific HTT-lowering profile. Around 30 close analogues of this hit were synthesized to reveal an active series that was shown to work via a unique HTT RNA-lowering mechanism. A review of this screening campaign and its output will be presented along with the characterisation studies aimed at understanding the mechanism of action of the hit series.